Cost‐effectiveness analysis of colorectal cancer screening using colonoscopy, fecal immunochemical test, and risk score. Issue 9 (26th March 2020) - Sekiguchi, Masau; Igarashi, Ataru; Sakamoto, Taku; Saito, Yutaka; Esaki, Minoru; Matsuda, Takahisa
Abstract: Background and Aim: A risk‐stratification score may be useful for colorectal cancer (CRC) screening, alongside screening colonoscopy (CS) and fecal immunochemical test (FIT). This study aimed to evaluate the effectiveness and cost‐effectiveness of population‐based CRC screening strategies using CS, FIT, and the Japanese CRC screening score. Methods: The effectiveness in quality‐adjusted life years (QALYs), cost‐effectiveness, and required number of CS procedures were evaluated for screening strategies with primary screening CS (strategy 1), FIT (strategy 2), and the risk score (strategy 3), using a simulation model analysis with two scenarios. In scenario 1, uptake rates for all tests were 60%. In scenario 2, uptake rates for FIT and a risk score were 40%, and those for screening CS and CS following a positive FIT or high risk score were 20% and 70%, respectively. Results: In scenario 1, strategy 1 gained the highest QALYs and required the highest cost. The incremental cost‐effectiveness ratios per QALY gained for strategy 1 against the others were lower than 5 000 000 JPY. Strategy 1 required more than twice as many CS procedures as the other strategies. In scenario 2, strategy 3 had the highest QALYs and lowest cost, and strategy 1 had the lowest QALYs and highest cost. Conclusions: Screening CS has the potential to be the most effective and cost‐effective form of CRC screening, although it requires a large number of CS procedures. However, if non‐invasive tests are preferred by recipients, other screening strategies, particularly those using the risk score, can be more effective and cost‐effective.